Analisis Penerapan Kedisiplinan dan Manajemen Kelas Pada Siswa Fase A Selama PLP di SD Negeri 81 Palembang - Nasywa Salsabila Putri; Echa Peritiwi; Vitara; Rifqi Fadhil Utbah (Yayasan Al-Afif, 2026)
This study aims to analyze the implementation of discipline and classroom management among Phase A students during the School Field Introduction Program (PLP) at SD Negeri 81 Palembang. The study employed a qualitative approach using direct observation during classroom learning activities. The findings revealed that students' discipline was still at an early stage of development, as indicated by behaviors such as lack of focus, frequent talking during lessons, and inconsistency in following classroom rules. Classroom management was implemented through the organization of the learning environment, time management, and instructional interactions. The discipline strategies applied included routine habituation, the establishment of simple classroom rules, and the provision of positive reinforcement. Furthermore, the study found that enjoyable and humanistic approaches were more effective in enhancing student engagement and discipline than authoritarian approaches. Internal factors, such as age, motivation, and students’ emotional conditions, as well as external factors, including teachers’ instructional styles and the learning environment, influenced the effectiveness of discipline implementation. Therefore, it can be concluded that successful learning in lower elementary grades is highly dependent on teachers’ ability to manage classrooms flexibly, communicate effectively, and foster students’ character development in a gradual and sustainable manner.